From Healthy Aging to Frailty: In Search of the Underlying Mechanisms - Brivio, Paola; Paladini, Maria S.; Racagni, Giorgio; Riva, Marco Andrea; Calabrese, Francesca; Molteni, Raffaella (Current Medicinal Chemistry, 2019)
Population aging is accelerating rapidly worldwide, from 461 million people older than 65 years in 2004 to an estimated 2 billion people by 2050, leading to critical implications for the planning and delivery of health and social care. The most problematic expression of population aging is the clinical condition of frailty, which is a state of increased vulnerability that develops as a consequence of the accumulation of microscopic damages in many physiological systems that lead to a striking and disproportionate change in health state, even after an apparently small insult. Since little is known about the biology of frailty, an important perspective to understand this phenomenon is to establish how the alterations that physiologically occur during a condition of healthy aging may instead promote cumulative decline with subsequent depletion of homoeostatic reserve and increase the vulnerability also after minor stressor events. In this context, the present review aims to provide a description of the molecular mechanisms that, by having a critical impact on behavior and neuronal function in aging, might be relevant for the development of frailty. Moreover, since these biological systems are also involved in the coping strategies set in motion to respond to environmental challenges, we propose a role for lifestyle stress as an important player to drive frailty in aging.
Keywords: neuroinflammation